The rights of people with disabilities under the law 02/09 - Guessas, Salim (Journal of Human Sciences, 2020)
The protection and recognition of the rights of persons with special needs are of the most important human rights obligations, as a group that requires community care and rehabilitation, which necessitates the recognition of their rights within arange of national and international legal texts.This is what the Algerian legislator said according to law N° :02-09 which the protection of peple with disabilitiesis a further step for ward in guarauteeing the rights of this  important –category of society, and to protect them from all forms of margina lization and in difference.